2023
DOI: 10.3389/fpubh.2022.1088590
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of blood cultures and antibiotic susceptibility testing for bacterial sepsis diagnosis and utilization of results by clinicians in Benin: A qualitative study

Abstract: ObjectivesWe assessed the current status of blood culture and antibiotic susceptibility testing (AST) practices in clinical laboratories in Benin, and how the laboratory results are used by physicians to prescribe antibiotics.MethodsThe qualitative study covered twenty-five clinical laboratories with a bacteriology unit and associated hospitals and pharmacies. Altogether 159 laboratory staff, physicians and pharmacists were interviewed about their perceptions of the state of laboratory diagnostics related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Before starting the training activities, a survey was conducted using face-to-face interviews with laboratory staff and physicians across the country to assess the training needs (14). The survey identified deficiencies in the knowledge and practices of laboratory technicians regarding culturing blood samples, identifying pathogens causing sepsis and AST.…”
Section: Identification Of the Training Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before starting the training activities, a survey was conducted using face-to-face interviews with laboratory staff and physicians across the country to assess the training needs (14). The survey identified deficiencies in the knowledge and practices of laboratory technicians regarding culturing blood samples, identifying pathogens causing sepsis and AST.…”
Section: Identification Of the Training Needsmentioning
confidence: 99%
“…The evaluation was carried out in the actual work situation and lasted 4 h in each laboratory. We had previously collected baseline information from the laboratories (14), which allowed us to assess the positive changes in the practices related to external and internal quality assurance, a blood culture, bacterial identification methods and AST. During the visits, the evaluators noticed that the new SOPs produced by the trainers were in effective use.…”
Section: Post-training On-site Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Benin have revealed poor hygiene in health facilities [ 13 , 14 , 15 ] and a lack of training of medical personnel in invasive procedures. To address this issue, various intervention projects in Benin aim to improve the technical skills of medical personnel [ 16 ]. However, there is no specific study that has analyzed the impact of these factors on the occurrence of infections.…”
Section: Introductionmentioning
confidence: 99%